IL-37 Confers Anti-Tumor Activity by Regulation of m6A Methylation - Mu, Xiaofeng; Zhao, Qi; Chen, Wen; Zhao, Yuxiang; Yan, Qing; Peng, Rui; Zhu, Jie; Yang, Chunrui; Lan, Ketao; Gu, Xiaosong; Wang, Ye (Frontiers in Oncology, 2021)
N6-methyladenosine (m6A) is a common transcriptomic modificationin cancer. Recently, it has been found to be involved in the regulation of non–small cell lung cancer (NSCLC) formation and metastasis. Interleukin 37 (IL-37) plays a crucial protective role in lung cancer. In our previous studies, we found that IL-37 is a potential novel tumor suppressor by inhibiting IL-6 expression to suppress STAT3 activation and decreasing epithelial-to-mesenchymal transition. Moreover, we found that treatment of IL-37 in lung cancer cells induced widespread and dynamic RNA m6A methylation. The effects of RNA m6A methylation of IL-37 treatment require further study. However, the functions of RNA m6A methylation of IL-37 treatment still await elucidation. Using MeRIP-seq and RNA-seq, we uncovered an unique m6A methylation profile in the treatment of IL-37 on the A549 cell line. We also showed the expression of m6A writers METTL3, METTL14, and WTAP and erasers ALKBH5 and FTO in A549 cells and lung cancer tissues after the treatment of IL-37. This study showed that IL-37 could lead to changes in m6A methylation level and related molecule expression level in A546 cells, and may downregulate the proliferation by inhibiting Wnt5a/5b pathway in A549 cells. We conclude that IL-37 suppresses tumor growth through regulation of RNA m6A methylation in lung cancer cells.